2019
DOI: 10.1634/theoncologist.2018-0805
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Barriers to Research Among Oncology Trainees in East Africa

Abstract: Background East Africa is one of the fastest growing regions in the world and faces a rising burden of cancer; however, few people are equipped to effectively conduct research in this area. Materials and Methods A 31‐item questionnaire was distributed to current trainees and recent graduates of the Master in Medicine in Clinical Oncology Program at Muhimbili University of Health and Allied Sciences in Tanzania. Areas that were assessed included (a) demographic information, (b) prior research training, (c) prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Post-graduate trainees expressed high motivation to incorporate research in their careers, although existing curriculums in terminal clinical degree programs do not emphasize research training. These findings echo our previous findings from an evaluation of oncology trainees in Tanzania, 11 demonstrating that this disconnect prevails across post-graduate training programs. Lack of training in research skills has been reported to hinder clinicians' involvement in research in both developed and developing countries, [32][33][34] highlighting the need for dedicated research training programs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Post-graduate trainees expressed high motivation to incorporate research in their careers, although existing curriculums in terminal clinical degree programs do not emphasize research training. These findings echo our previous findings from an evaluation of oncology trainees in Tanzania, 11 demonstrating that this disconnect prevails across post-graduate training programs. Lack of training in research skills has been reported to hinder clinicians' involvement in research in both developed and developing countries, [32][33][34] highlighting the need for dedicated research training programs.…”
Section: Discussionsupporting
confidence: 89%
“…Different qualitative data collection methods were utilized and involved different groups of participants with the aim of collecting wider views on the different themes and draw harmonized conclusions/opinions/suggestions. 11 , 13 , 14 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, cancer research is still scarce in the continent to meet this public health challenge and few people are equipped to conduct research in the area despite remarkable progress in building human research capacity over the last decade [7, 112, 113]. In Tanzania, a great part of oncology trainees would like to incorporate research into their careers, but inadequate training in research methodology and absence of longitudinal mentorship is a drawback [114].…”
Section: Cancer Research Prevention and Health Care Resources In Aoccmentioning
confidence: 99%